Violence, gender and the price of beer in England and Wales - Kent Matthews; Jonathan Shepherd; Vaseekaran Sivarajasingham; Sally Benbow (Cardiff University, Cardiff Business School, 2006)
This paper examines the influence of the real price of beer on violence-related injuries split by gender across the economic regions in England and Wales. It was concluded that alcohol prices and injury sustained in violence is causally related in both males and females. Injury of females is causally related to poverty but injury of males. However, nationwide sports events were associated only with male assault injury. Violence-related harm was significantly and independently linked to other socioeconomic and demographic factors. Our results suggest that the real price of alcohol (using beer as an example) has a part to play in controlling the consumption of alcohol and the incidence of violent injury.
Keywords: K40; I30; C50; 330; Alcohol; gender; violence; price of beer